China and its national minorities autonomy or assimilationß - Heberer, Thomas 1947- (Taylor & Francis Group, 2018)
"This title was first published in 1990: This book is a study of past and present policies of the People's Republic of China towards its numerous and varied minority groups, a subject about which there is scant information in the West. It examines the impact of Chinese culture on these diverse groups and China's attempt to bring them into the mainstream of Han life. The impact of the Cultural Revolution on the minority peoples, the future of Tibet, and the implications of Chinese minorities policies for Sino-Soviet relations are among the topics discussed in this book."--Provided by publisher
First published 1989 by M.E. Sharpe. - Includes bibliographical references (pages 147-155) and index
Keywords: Geschichte 1949-1982; Minderheitenpolitik; Entwicklungspolitik; Nationalitätenpolitik; Nationale Minderheit; China; Ethnology / China; China / Ethnic relations / Electronic books